E-educational platforms and their role in achieving school reform from the teacher's Perspectives in light of the distance education experience (Madrasati platform as a model) - Al-Ansary, Rofaydah Adnan (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to shed light on the current status of the use of e-educational platforms and their role in achieving (school reform from the teacher's perspectives in light of the distance education experience (my school platform as a model). Descriptive survey approach was adopted. The study sample consisted of 95 female teachers who were selected using a simple random sampling method. Many statistical analysis tools were used to elicit the study findings such as frequencies, menas, and standard deviation. The results showed the participants' attitudes towards Madrasati platform and available opportunities were high, while their attudes towards obstacles were moderate. Results also revealed that there were no statistically significant differences for the school stage variable to the three sections of the study tool (trends, obstacles, and opportunities), idicating the pivotal role of e-educational platforms in achieving school reform. The study has concluded with the results and proposals obtained.
Keywords: online platforms; school reform; teacher; distance education; Madrasati platform